PERKOSAAN DALAM PERKAWINAN SEBAGAI TINDAK PIDANA - Putri Ayu Lestari; Wiwik Afifah (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
There are so many cases of sexual violence that are not reported to law enforcement officials, or have even been reported but rejected. Among them is rape in marriage. This happens because sexual relations carried out in marriage are considered as common things that husbands do to their wives, because they occur in legal marriages. This study aims to determine marital rape as a crime. The research method uses normative juridical. This research approach uses legislation and conceptual. Based on research, marital rape has not been clearly regulated in the Criminal Code (KUHP). However, it has been regulated in Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT). Meanwhile, the husband's actions towards his wife can be said to be marital rape if there are elements of coercion, threats, and violence without regard to the interests of the wife. This is reinforced by Islamic law, namely in the letter Al-Baqarah Verse 223